Poluição marinha por microplásticos e os impactos na saúde humana : desafios jurídicos ambientais sob a perspectiva do consumo sustentável - Isse, Jordana (My University, 2026)
Falling within the scope of Environmental Law and Consumer Law, this dissertation aims to present the challenge faced by the Brazilian legal system and identify possible alternatives to this process from an environmental perspective, justified by the presence of microplastics in the ocean'as evidenced by the natural sciences and the risks to human health. To this end, the study seeks to analyze the legal responses that Brazilian law offers to the obstacles posed by these plastic micro-particles and the consequences of this fragmented pollution, which spills over into the ocean. Furthermore, it addresses the issue of sustainable consumption through the principle of environmental information and the responsibility of public authorities and the community in defending the environment. The methodology to be applied to this dissertation will be outlined through its method, aims, purpose, objectives, and means. In addition to exploratory bibliographic research, the analytical-normative method?of a deductive nature will be adopted, incorporating the hypothetical-deductive method, which is characterized by the establishment of assumptions that will be subjected to testing and criticism, as well as comparison with facts. Regarding the approach, a qualitative research design is envisaged, aiming to investigate possible gaps in the national legal framework from the perspective of marine pollution by microplastics and consumer health safety. To understand the impacts of marine pollution caused by microplastics, their origin and presence in consumer products and services will be explored, covering the history of plastic and extending to evidence of their impact on the marine environment, the food chain, and the human body. Thus, although Brazil has a robust legal framework, solid waste management policies, and marine protection measures against plastic pollution, the specific issue of microplastics is not addressed in the legal system. However, there is a gap regarding the implementation of the fundamental principles of environmental law and consumer law, reinforcing the need for clear and accurate information for consumers about these plastic particles present in products and services. Improving regulation requires the government to promote standards that disclose the presence of microplastics in products and services through labeling, fostering conscious consumption and reinforcing the need for the effective implementation of a circular economy system to safeguard marine biodiversity. [resumo fornecido pelo autor]
Inserido no âmbito do Direito Ambiental e do Direito do Consumidor, essa dissertação tem por objetivo apresentar o desafio enfrentado pelo ordenamento jurídico brasileiro e identificar possíveis alternativas a esse processo, em um viés ambiental, justificado pela presença evidenciada pela ciência natural de microplásticos no oceano e os riscos à saúde humana. Para tanto, pretende-se analisar quais são as respostas jurídicas que o direito brasileiro oferece aos obstáculos impostos por estas micropartículas de plásticos e as consequências dessa poluição fragmentada, que transborda no oceano. Ademais, enfrenta a questão do consumo sustentável, por meio do princípio à informação ambiental e da responsabilidade do poder público e da coletividade na defesa do meio ambiente. Como metodologia a ser aplicada a essa dissertação será exposta através de seu método, anseios, finalidade, objetivos e meios. Para além da técnica de pesquisa exploratória bibliográfica, adotará como método de pesquisa o analítico-normativo, de natureza dedutiva, perpassando pelo método hipotético-dedutivo, o qual caracteriza-se pelo estabelecimento de suposições, as quais serão submetidas a testes e críticas, assim como ao confronto com fatos. Com relação à abordagem, vislumbra-se uma pesquisa qualitativa, propondo-se investigar possíveis lacunas no ordenamento jurídico pátrio, sob o prisma da poluição marinha por microplásticos e a segurança da saúde do consumidor. Para compreender os impactos da poluição marinha por microplásticos, sua origem e presença em produtos e serviços de consumo será explorada, perpassando pela história do plástico, até as evidências de sua incidência no meio ambiente marinho, na cadeia alimentar e no corpo humano. Dessarte, apesar do Brasil dispor de um robusto arcabouço legal, de políticas de gestão de resíduos sólidos e de proteção marinha contra a poluição plástica, a questão específica dos microplásticos não está disposta no sistema jurídico. Todavia, há uma lacuna referente à efetivação dos princípios basilares do direito ambiental e do direito do consumidor, reforçando a necessidade de informações claras e precisas ao consumidor sobre essas partículas plásticas inseridas nos produtos e serviços. O aperfeiçoamento da regulação requer, por parte do Estado, o incentivo às normas que informem a existência de microplásticos em produtos e serviços, através de rótulos, fomentando o consumo consciente, reforçando a necessidade da implementação efetiva de um sistema circular, como salvaguarda à biodiversidade marinha. [resumo fornecido pelo autor]
Keywords: Sociedade de consumo -Aspectos jurídicos; Desenvolvimento sustentável; Direito ambiental; Meio ambiente; Poluição marinha; Consumer society - Legal aspects; Sustainable development; Environmental law; Environment; Marine pollution